The Self-Government of Students in the Theory and Practice of „Active School” - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2001)
This article shows the standpoint of “active school” to the students self-government in the end of XIX –beg. of XX century in the USA and West Europe. Theoretical discussions about qualities and shortcomings of self-government of many authors - J. Dewey, R.Cousinet, A. Ferriere, J. Piaget et al., - are presented in this article. Author also presents the experience of “new schools” of instilling the self-government in the practice.
Keywords: History of education; self-government of Students; “Active School”; J. Dewey; A. Ferriere.